2009
DOI: 10.1016/j.crohns.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pseudotumor of the liver associated with Crohn's disease

Abstract: Inflammatory liver pseudotumor is a rare entity. Associations with several inflammatory conditions were reported but association with inflammatory bowel disease is unusual. We report the case of liver inflammatory pseudotumor occurring in the course of Crohn's disease in a 23-year-old woman and treated conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The stomach and omentum are the predominant sites, followed by the small intestine, colon, and oesophagus [8] . Colonic IPTs, although rare, have been documented in association with Crohn's disease and chronic diverticulitis [3] , [5] , [12] . A review of colonic IPTs conducted in 2015 found only 18 prior literature records of IPTs in the colon [13] .…”
Section: Discussionmentioning
confidence: 99%
“…The stomach and omentum are the predominant sites, followed by the small intestine, colon, and oesophagus [8] . Colonic IPTs, although rare, have been documented in association with Crohn's disease and chronic diverticulitis [3] , [5] , [12] . A review of colonic IPTs conducted in 2015 found only 18 prior literature records of IPTs in the colon [13] .…”
Section: Discussionmentioning
confidence: 99%